Neuroscience of cancer: unraveling the complex interplay between the nervous system, the tumor and the tumor immune microenvironment - Qibo Huang; Bai Hu; Ping Zhang; Ye Yuan; Shiwei Yue; Xiaoping Chen; Junnan Liang; Zhouping Tang; Bixiang Zhang (Molecular Cancer)
Abstract The study of the multifaceted interactions between neuroscience and cancer is an emerging field with significant implications for understanding tumor biology and the innovation in therapeutic approaches. Increasing evidence suggests that neurological functions are connected with tumorigenesis. In particular, the peripheral and central nervous systems, synapse, neurotransmitters, and neurotrophins affect tumor progression and metastasis through various regulatory approaches and the tumor immune microenvironment. In this review, we summarized the neurological functions that affect tumorigenesis and metastasis, which are controlled by the central and peripheral nervous systems. We also explored the roles of neurotransmitters and neurotrophins in cancer progression. Moreover, we examined the interplay between the nervous system and the tumor immune microenvironment. We have also identified drugs that target the nervous system for cancer treatment. In this review we present the work supporting that therapeutic agent targeting the nervous system could have significant potential to improve cancer therapy.